Pemanfaatan dan Konservasi Toga sebagai Upaya Peningkatan Ekonomi di Desa Waung Kecamatan Krembung Kabupaten Sidoarjo - Cindi Erlin Carlita; Akhmad Nafik; Rahmad Budianto; Siti Syefiana Fatmawati; Intan Eka Wulandari; Mochamad Hanafi; Muhammad Abdul Ghofir; Ahmad Hamdani Muslim; Cindy Dwi Cahyani; Muhammad Naufal Ilhami; Bahauddin Alqostolani; Abdul Gofur; Medya Ayunda Fitri (Journal of Science and Social Development, 2023)
Waung Village is one of the villages located in Krembung District, Sidoarjo Regency which has great potential in the development and conservation of toga. However, residents still have not optimized this potential. The aim of carrying out the Unusida HMTK PPK is as a form of synergy between students and the community to optimize the potential that exists in the village and create a healthy society. The activities carried out include socialization of the program, mapping of the biodiversity potential of medicinal plants in the village, training in planting and conservation of toga, as well as development of processing of toga products. The results of the implementation of the activities that have been carried out are the formation of a toga conservation area and the development of processed toga products in the form of telang syrup, telang chocolate and dry tea